Empirical study on improving teacher performance with organizational culture and compensation - Ulum, Bachrul; Nawawi, Nawawi; Aldiansyah, Agung; Haryadi, Didit (Trigin Publisher, 2024)
Organizations can achieve success through their resources, especially human resources. Therefore, employees become the driving force in making a real contribution to the organization's success on an ongoing basis. This study aims to determine the variables that affect teacher performance and develop a theoretical basis and research model. This study used the associative descriptive quantitative method with a population of 37 respondents drawn into samples using non-probability sampling using saturated sampling / total sampling methods—data analysis techniques using linear regression with the help of SPSS software version 26. The results of this study show that the first hypothesis is that organizational culture affects teacher performance. Thus, the second hypothesis states that teacher performance is affected by compensation, meaning that the more appropriate the prize, the more teacher performance increases. The third hypothesis is that teacher performance is influenced by organizational culture and balance that can simultaneously improve teacher performance. This research is expected to make theoretical contributions to the literature in this context, certainly in the context of human resource management.